The Correlation of Teachers’ Reinforcement and Students’ Achievement in English Learning Process - Fajrin, Nurul Hidayati; Kustati, Martin; Yustina, Luli Sari (Turast: Jurnal Penelitian dan Pengabdian, 2019)
Teachers have to do several actions in the class such us encouragement, reinforcement, reward, and punishment. In this case researchers focuses on reinforcement. One of the class managements’ indicator is teacher gives reinforcement and feedback to students’ responses and students’ achievement as long as Learning Process. The study aims to identify teachers’ reinforcement in English Learning Process at Senior High School 1 Padang. A quantitative research was used where the data taken from questionnaire. It was focused on positive and negative reinforcement that used in English Learning Process and any significant correlation of teacher’ reinforcement and students’ achievement. The data was analyzed by using Pearson correlation. Based on the statement above, it can be concluded that all of the positive and negative reinforcement used by English teacher at Senior High School 1 Padang and the mostly used is positive reinforcement. The finding is there is significance correlation of teachers’ reinforcement and students’ achievement in English Learning Process.  All of the teachers are expected that using reinforcement in English Learning Process due to increased the students’ achievement